Improving Medical Students’ Confidence in Performing Mental State Examinations: A Quality Improvement Project Using Creative and Narrative Teaching Methods, Video-Based Learning, and Documentation Practice - Clara Seipt; James Anderson (BJPsych Open)
Aims: Starting a new role as Clinical Teaching Fellows, early student feedback identified a gap between students’ academic understanding of the Mental State Examination (MSE), and confidence in its application and interpretation. Assessors recognised similar uncertainty in students regarding findings in the MSE, and a lack of confidence in presenting. This project aimed to improve medical students’ self-reported confidence in the MSE via an interactive workshop. Each PDSA cycle, we aimed to implement feedback suggestions through creative teaching methods, to improve confidence, engagement, and interaction in the MSE teaching.